The The effectiveness of galangal Alpinia galanga extract for the treatment of sangkuriang catfish Clarias gariepinus infected Aeromonas hydrophila - Yuli Andriani; Desy Setyo Wati; Irfan Zidni; Roffi Grandiosa Herman (Jurnal Akuakultur Indonesia)
The purpose of this research is to find out the optimal dose of galangal extract to treatment of Sangkuriang catfish infected with Aeromonas hydrophila, the fish fry used are 5-7 cm in size. October-November 2022 was the research was carried out by an experimental method using a completely randomized design (CRD) with four treatments and three replications. The treatment used was immersing with galangal extract for 24 hours with doses of 0 mg/L (A), 250 mg/L (B), 500 mg/L (C) and 750 mg/L (D). Maintenance of test fish for 14 days. Aeromonas hydrophila bacteria are used to infect fish with a density of 108 CFU/ml by immersing 10 ml in 10 liters of water. Clinical symptoms of infection, clinical symptoms of recovery period, survival rate and water quality were used as parameters in this research. The results showed that the use of galangal extract for treatment of Sangkuriang catfish fry infected with Aeromonas hydrophila by immersion method for 24 hours at a concentration of 500 mg/L was the best treatment with the survival rate of 90%.